KEMAMPUAN ADAPTASI SISTEM KEUANGAN DESA (SISKEUDES) DI DESA LARANGAN KECAMATAN CANDI KABUPATEN SIDOARJO - Ilmi Usrotin Choiriyah; Siti Fatima Sabilillah; Ahmad Riyadh (Universitas Tribhuwana Tunggadewi, 2022)
Adaptability must be possessed by every sector in order to survive with changes in information and communication technology. The government takes advantage of this change through E-Government, namely the Village Financial System. The Larangan Village Government has implemented Village Financial System but there are still problems, namely human resources have not been fully able to adapt to Village Financial System even though they have been given technical guidance, and internet network facilities are slow so Village Financial System often has errors. The purpose of this study was to determine the adaptability of the Village Financial System Village Financial System in the Larangan Village, Candi District, Sidoarjo Regency. The research method uses descriptive qualitative research. Data collection techniques using interviews, observation, and documentation. The data analysis technique uses data collection, data reduction, data presentation and drawing conclusions. The results of the study show that the adaptability of SISKEUDES still has obstacles such as a slow internet network, limited staff who control SISKEUDES operations, and technical guidance from the Regency Government through the Development Finance Supervisory Agency which is considered not optimal.AbstrakKemampuan adaptasi harus dimiliki oleh setiap sektor agar dapat bertahan dengan perubahan teknologi informasi dan komunikasi. Pemerintah memanfaatkan perubahan tersebut melalui E-Government yaitu Sistem Keuangan Desa. Pemerintah Desa Larangan telah menerapkan Sistem Keuangan Desa tetapi masih terdapat permasalahan yaitu sumber daya manusia belum sepenuhnya mampu beradaptasi dengan Sistem Keuangan Desa walaupun telah diberikan bimbingan teknis, dan sarana jaringan internet yang lambat sehingga Sistem Keuangan Desa sering error. Tujuan penelitian ini ialah untuk mengetahui kemampuan adaptasi Sistem Keuangan Desa di Desa Larangan Kecamatan Candi Kabupaten Sidoarjo. Metode penelitian menggunakan penelitian deskriptif kualitatif. Teknik pengumpulan data menggunakan wawancara, observasi, dan dokumentasi. Teknik analisis data menggunakan pengumpulan data, reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian menunjukan bahwa kemampuan adaptasi SISKEUDES masih terdapat kendala seperti jaringan internet yang lambat, keterbatasan pegawai yang menguasai operasional SISKEUDES, dan bimtek dari Pemerintah Kabupaten melalui Badan Pengawasan Keuangan Pembangunan yang belum maksimal.